Gambaran CT Scan Thorax pada Sampel Terkonfirmasi Covid-19 - Syahrir Syahrir; Muhammad Fahrul M.; Sitti Normawati; Nurhasmi Nurhasmi (Lontara Journal of Health Science and Technology, 2022)
Thorax photos with CT scans can be used to monitor development and diagnose lung abnormalities due to COVID-19. This study aims to find out the results of CT Scan Thorax analysis of COVID-19 patients. The number of samples used as many as 30 samples using quantitative research methods with a descriptive approach. The results in this study showed from 30 samples 80% there is a picture of Pneumonia with other images such as GGO, Consolidation and accompanied by water bronchogram, Crazy Paving, and Halo Sign.